Technical efficiency of onion production: The case of smallholder farmers in Dallo Mena district, Bale zone, Oromia national regional state, Ethiopia - Gemechu Mulatu; Tassew Gemechu (Cogent Business & Management, 2023)
This study was intended to identify factors affecting the technical efficiency of onion production by smallholder farmers in Dallo-Manna district of south eastern Ethiopia using cross-sectional data obtained from 183 randomly selected smallholder farmers. Both descriptive statistics and econometric models were used for data analysis. Cobb-Douglas stochastic frontier production function was fitted to predict the technical efficiency of onion-producing farmers. The mean of technical efficiencies of farmers in the study area was 76% and this indicates that there is room for improvement in onion production. The Tobit regression model was fitted to identify factors influencing technical efficiency scores and the result indicated that the technical efficiency of onion production was statistically and significantly influenced by the experience of household head in onion production, education level, family size, livestock holding size, access to market information, number of weeding, training, and extension contact. However, land fragmentation and access to credit services were negatively and statistically significantly affected the level of technical efficiency of onion production. In general, there is a need to intervene in expanding the educational sector, provision of training, and extension services and solving the problem of land fragmentations.
Keywords: 650; Ethiopia; frontier; onion production; smallholders; cobb-douglas; technical efficiency